SIGNIFIKANSI PENGUATAN EKONOMI UMAT BERBASIS MODERASI BERAGAMA PADA UMKM DI KOTA MEDAN - M. Syukri Albani Nasution; Angga Syahputra; Wulan Dayu; Reni Ria Armayani (LPPM Universitas Bina Bangsa, 2023)
This research discusses the economic empowerment of people based on religious moderation in Micro, Small and Medium Enterprises (MSMEs) in Medan City, Indonesia. With a large Muslim population, it is important to understand and apply the values of religious moderation in the economic activities of the community. This research proposes a holistic approach, involving mentoring the MSME community through surveys, socialization, training, and ongoing mentoring through WhatsApp groups. Through survey activities, MSME actors were identified and understood their needs and expectations regarding religious moderation training. Socialization involving lectures and role plays deepened participants' understanding, while practical training taught the application of religious moderation values in daily business. Ongoing mentoring through WhatsApp groups enabled continuous interaction, discussion and support among participants. Evaluation results showed a significant increase in participants' knowledge after the training. The training also created an inclusive and ethical business environment, enhanced business collaboration, and strengthened relationships with customers and business partners. The government's role in socializing the values of religious moderation is important to prevent religious conflict and build an inclusive and harmonious society. This research proposes that religious moderation should be a guiding principle in every aspect of life, including in the business world, to create a society of character and mutual respect